Phenological and Pomological Characteristics of Native Apple (Malus domestica Borkh) Cultivars of Trans Himalayan Ladakh India - Dolkar, Tsetan; Kumar, Deepak; Chandel, Joginder S.; Angmo, Spalzin; Chaurasia, O.P.; Stobdan, Tsering (Defence Life Science Journal, 2021)
Seven local apple cultivars of the trans-Himalayan Ladakh region were studied for phenological and pomological characteristics. Early and extended flowering was observed. Flowering began 12 days earlier as compared to Royal Delicious, a popular introduced cultivar. The cultivars attained fruit maturity between mid-August to early September, which is one month earlier than Royal Delicious. Apples of the Ladakh region are soft (6.1±1.1 kg cm-2) and small in size (60.1±29.1 g). The unique characteristics observed in apples of the Ladakh region, such as early flowering and early fruit maturity offer an opportunity for exploring the native cultivars for future breeding programs for the development of early maturing cultivars.